Deep‐Penetrating Triple‐Responsive Prodrug Nanosensitizer Actuates Efficient Chemoradiotherapy in Pancreatic Ductal Adenocarcinoma Models. Issue 31 (9th July 2022) - Tang, Xiaohu; Du, Xiaomeng; Yu, Yanting; Qin, Meng; Qian, Lili; Zhang, Meng; Yang, Yan; Yu, Qingsong; Gan, Zhihua
Abstract: Chemoradiotherapy (CRT) is the most accepted treatment for locally advanced pancreatic ductal adenocarcinoma (PDAC) and can significantly improve the R0 resection rate. However, there are few long‐term survivors after CRT. Although some polymer nanoparticles have shown potential in alleviating the dose‐limiting toxicity and assisting the chemotherapy of PDAC, there are few efficient nanosensitizers (NS) available for CRT of this malignancy, especially in the context of its hypoxic nature. Herein, based on the biological features of PDAC, a γ‐glutamyl transpeptidase (GGT)/glutathione (GSH)/hypoxia triple‐responsive prodrug NS to overcome the biological barrier and microenvironmental limitations confronted by CRT in PDAC is developed. Due to triple‐responsiveness, deep tumor penetration, GSH/hypoxia‐responsive drug release/activation, and hypoxia‐induced chemoradio‐sensitization can be simultaneously achieved with this NS. As a result, tumor shrinkage after CRT with this NS can be observed in both subcutaneous and orthotopic PDAC models, foreshadowing its potential in clinical neoadjuvant CRT. Abstract : γ‐Glutamyl transpeptidase (GGT)/glutathione (GSH)/hypoxia triple‐responsive prodrug nanosensitizer based on metronidazole‐modified Pt(IV) prodrug and GSH‐responsive metronidazole polymer efficiently penetrates dense pancreatic ductal adenocarcinoma (PDAC) tissue via GGT‐activated transcytosis, releases loaded drugs in response to GSH/hypoxia, achieves efficient hypoxic chemoradio‐sensitization, and inhibits both tumor growth and metastasis.